To analyze the growth rates of the sequences for \( f(x) = 2 \cdot 2^x \) and \( g(x) = 10x + 2 \), let’s look closely at their behavior.
-
Evaluate the difference between terms:
-
For \( f(x) = 2 \cdot 2^x \):
- \( f(1) = 4 \)
- \( f(2) = 8 \) (Difference = 4)
- \( f(3) = 16 \) (Difference = 8)
- \( f(4) = 32 \) (Difference = 16)
- \( f(5) = 64 \) (Difference = 32)
- \( f(6) = 128 \) (Difference = 64)
- \( f(7) = 256 \) (Difference = 128)
- \( f(8) = 512 \) (Difference = 256)
- \( f(9) = 1024 \) (Difference = 512)
-
For \( g(x) = 10x + 2 \):
- \( g(1) = 12 \)
- \( g(2) = 22 \) (Difference = 10)
- \( g(3) = 32 \) (Difference = 10)
- \( g(4) = 42 \) (Difference = 10)
- \( g(5) = 52 \) (Difference = 10)
- \( g(6) = 62 \) (Difference = 10)
- \( g(7) = 72 \) (Difference = 10)
- \( g(8) = 82 \) (Difference = 10)
- \( g(9) = 92 \) (Difference = 10)
-
-
Calculate the growth rates in intervals:
- For \( f(x) \): The growth rates are doubling each time (4, 8, 16, ...).
- For \( g(x) \): The growth is linear with a constant difference of 10 for each subsequent term.
-
Compare the sequences:
- Initially (Term 1: \( f(1)=4 \) and \( g(1)=12 \)), \( g(x) \) is greater.
- Between terms:
- From Term 1 to Term 2 (4 to 8 for \( f(x) \), 12 to 22 for \( g(x) \)) shows \( g(x) \) is higher.
- By Term 3, \( f(3) = 16 \) and \( g(3) = 32 \), still \( g(x) \) is higher.
- At Term 4, \( f(4) = 32 \) and \( g(4) = 42 \), still \( g(x) \) is higher.
- At Term 5, \( f(5) = 64 \) vs \( g(5) = 52 \), here \( f(x) \) surpasses \( g(x) \).
-
Conclusions about Statements:
- Statement #1: True - \( f(x) \) eventually surpasses \( g(x) \).
- Statement #2: False - \( g(x) \) is always higher until Term 5.
- Statement #3: False - \( f(x) \) surpasses \( g(x) \), not the other way around.
Thus, the true statement is Statement #1.
Final answer: Statement #1 is true.